Sport involvement and academic achievement among UiTM Samarahan sports science students / Floranordiana Ennya Niru - Niru, Floranordiana Ennya (2020)
Sports involvement is found to offer several positive effects on physical health, mental health and influences academic achievement by modifying both brain structure and function. The purpose of this study was to investigate the relationship between Sport involvement and acdemic achievement among UiTM samarahan sports science students. A total of 213 respondents (N=213) sports science students were chosen. The frequency of sport involvement by Adachi and willoughby (2013) instrument were used to collect the data. The finding shows that there was no significant relationship between sport involvement and academic achievement (r = .041). The finding of this study shows that sport involvement and academic achievement among UiTM Samarahan sport science students were not correlated to each other. The good academic achievement is not the result of active involvement in sport but rather is beacuse the students have good time management and also because of university is effective in scheduling classes and providing good learning systems and attractive incentives to motivate the sport science students.